2021
DOI: 10.1002/qj.4100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the AROME model's ability to represent ice crystal icing using in situ observations from the HAIC 2015 field campaign

Abstract: Since pilots generally avoid intense convective areas, ice crystals icing (ICI) is an aeronautical weather incident that mainly occurs in the anvil of tropical deep convective clouds. Samples of favorable conditions for the occurrence of ICI and data from the High Altitude Ice Crystals (HAIC) 2015 field campaign in French Guiana are investigated and compared with simulations of the French operational mesoscale forecast system Application of Research to Operations at Mesoscales (AROME). To this end, a contextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…In this Figure 8, dots in the lower-right region of each graph correspond to ICI-prone conditions, especially those with colder temperatures. Dots where median TWC is higher than 0.5 g⋅m −3 and where Contrary to what has been sampled during the 2015 HAIC field campaign, very few ICI-favourable conditions were simulated in OPER (Wurtz et al, 2021) and Vt (not shown). Nevertheless, in the HAIC experiment, many more ICI-prone conditions are simulated (Figure 8).…”
Section: Analysis Of the Sensitivity Tests For The Haic-201periodmentioning
confidence: 95%
See 4 more Smart Citations
“…In this Figure 8, dots in the lower-right region of each graph correspond to ICI-prone conditions, especially those with colder temperatures. Dots where median TWC is higher than 0.5 g⋅m −3 and where Contrary to what has been sampled during the 2015 HAIC field campaign, very few ICI-favourable conditions were simulated in OPER (Wurtz et al, 2021) and Vt (not shown). Nevertheless, in the HAIC experiment, many more ICI-prone conditions are simulated (Figure 8).…”
Section: Analysis Of the Sensitivity Tests For The Haic-201periodmentioning
confidence: 95%
“…These aggregates are represented in ICE3 by the snow category and represent indeed the majority of ice content in simulated anvil clouds. Following Wurtz et al (2021), different experiments were launched using the modifications described hereafter and are summed up in Table 3. These modifications are based on diagnostics derived from observations.…”
Section: Description Of Sensitivity Testsmentioning
confidence: 99%
See 3 more Smart Citations